FRI0682 Follow-up of treatment response with dynamic doppler ultrasound in raynaud'sphenomenon. (15th June 2017) - Toprak, U; Ozbalkan, Z; Edugan, M; Parlak, S; Sandıkci, SC; Kaya, T; Saylisoy, S
Abstract : Background: This study aims to investigate the role of flow parameters obtained by dynamic Doppler ultrasound in the objective follow-up of treatment response in Raynaud's phenomenon (RP) cases. Methods: The study included newly diagnosed 33 patients with primary RP (PRP), 31 patients with secondary RP (SRP), and 26 healthy controls. The control group was evaluated with Doppler once, while the patients before treatment and on the third month of thet reatment. Baseline and post-cold provocation diameter (BD, CPD, mm) andflowvolume (BFV, CPFV, mL/min); post-coldprovocationflowstarting time (FST, min), and flowv olume normalizing time (FVNT, min) were recorded. Statistical analysis: for disturubution of thes ex of the groups: chi-square test, for analysing age distrubution among the groups One-way ANNOVA; for analysing the pre and post treatment doppler results: Wilcoxon test and fo rcomparison of the PRP and SRP post treatment values to control group; Krusal Wallis test were used. A p value less than 0, 05 was considered statistically significant. Results: Before-after treatment, there was no significant improvement in the BD in both PRP and SRP groups (0.79±0.17–0.82±0.19 vs. 0.66±0.13–0.68±0.14 PRP vs. SRP, respectively), while FST did not significantly improve in the PRP group (1.15±2.27–0.61±1.41 vs 3.13±4.81–1.58±2.36) (p>0.05). A significant improvement was observed in baseline flow volüme (3.08±2, 96 vs 3.91±3.39 (p: 0, 002), flow volume normalization time (7.24±7.60 vs 3.84±3.39) (p: 0, 0001), after cold provocation flow volume (1.18±1, 26 vs 2.17±2.16) (p: 0, 0001), after cold provocated diameter (0.63±0.15 vs 0.70±0.16) (p: 0, 005) in PRP group after treatment. In SRP group, only baselined iameter changes were not influenced by the treatment, all other post treatmen tparameters were impoved in all SRP cases including baseline flow volume (2.14±1.94 vs 2.80±2.15) (p:0, 009), after cold provocation diameter (0.56±0.15 vs 0.63±0.13) (p: 0.004), after cold provocation flow volume (1.07±1.40 vs 1.46±1.67) (p: 0, 004), flow starting time (3.13±4.81 vs 1.58±2.36) (p: 0, 021) and flow volume normalisation time (9.58±8.49 vs 4.32±3.56) (p: 0, 0001). There was an improvement in parameters after the treatment in both RP groups comparing by the control groups (p<0.01). Conclusions: Doppler ultrasound is an objective, cost-effective, safe (does not include radiation), and easy-to-use method in thefollow-up of RP patients on macrovascular level with or without cold provocation before and after treatment. Acknowledgements: Keywords: Raynoud Phenomenon, treatment, Doppler ultrasound Disclosure of Interest: None declared